CHILD-CENTERED METHODFOR TEACHING ENGLISH TO YOUNG LEARNERS(A CASE STUDY OF THE IMPLEMENTATION OF ENGLISH TEACHING METHODS IN TWO ELEMENTARY SCHOOLS IN WESTERN BANDUNG AREA, WEST JAVA) - Piesesha Hartiyana, - (2008)
Child-centered method is believed to be ideal for teaching English to young learners. However, English teachers in Indonesia rely much on grammar-translation method that neglects meaningfulness and children learning characteristics, the core aspects of child-centered method. To portray the methods implemented by English teachers in Indonesian context, three teachers from two schools in Western Bandung were observed and interviewed. Their syllabus and lesson plans were also analyzed to see their preferences for teaching methods. This paper examines whether the methods employed by the three teachers are in line with child-centered method. The result shows that T1 combined Grammar-translation method with Total Physical Response method, while T2 combined Grammar-translation method with Audio-lingual method. Both teachers disregarded the aspect of meaningfulness and thus set aside the development of their students' learning potential. On the other hand, T3, being in favor for Total Physical Response method, attempted to practice some values close to child-centered method. Considering the urgency of promoting meaningful teaching practices to English teachers in Indonesia, socialization efforts, e.g. teacher trainings, seminars, or workshops, on child-centered method are required.